Carotenoids in Staple Cereals: Metabolism, Regulation, and Genetic Manipulation - Zhai, Shengnan; Xia, Xianchun; He, Zhonghu (Frontiers in Plant Science, 2016)
Carotenoids play a critical role in animal and human health. Animals and humans are unable to synthesize carotenoids de novo, and therefore rely upon diet as sources of these compounds. However, major staple cereals often contain only small amounts of carotenoids in their grain. Consequently, there is considerable interest in genetic manipulation of carotenoid content in cereal grain. In this review, we focus on carotenoid metabolism and regulation in non-green plant tissues, as well as genetic manipulation in staple cereals such as rice, maize, and wheat. Significant progress has been made in three aspects: (1) seven carotenogenes play vital roles in carotenoid regulation in non-green plant tissues, including DXS (1-deoxyxylulose-5-phosphate synthase) influencing isoprenoid precursor supply, PSY (phytoene synthase), LCYB (β-cyclase) and LCYE (ε-cyclase) controlling biosynthesis, HYDB (1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate reductase) and CCDs (carotenoid cleavage dioxygenases) responsible for degradation, and OR (orange) conditioning sequestration sink; (2) pro-vitamin A-biofortified crops, such as rice and maize, were developed by either metabolic engineering or marker-assisted breeding; (3) QTLs for carotenoid content on chromosomes 3B, 7A, and 7B were consistently identified, eight carotenogenes including 23 loci were detected, and ten gene-specific markers for carotenoid accumulation were developed and applied in wheat improvement. A comprehensive and deeper understanding of the regulatory mechanisms of carotenoid metabolism in crops will be benefitical in improving our precision in improving carotenoid contents. Genomic selection and gene editing are emerging as transformative technologies for vitamin A biofortification.